The determinants of capital structure: evaluation between Shariah - compliant and conventional companies - Mohmad Hassan, Nadia Nurul Najwa; Mohamad Shafi, Roslina; Mohamed, Suhana (2012)
Islamic financial markets are still at infant stage in Malaysian economy, thus have created dual-economic financial systems which are Islamic and conventional financial system. The capital structure determinants between shariah-compliant and conventional companies might be different. The aim of this research was to disclose the factors that influence capital structure of shariah-compliant and conventional companies. By using multiple regressions, we examined 58 companies listed on the Main Market of Bursa Malaysia from year 2005 until 2010. We found that the shariah-compliant companies' debt ratio was significant with profitability, size and non-debt tax shield while profitability and tangibility play significant role in capital structure decision of conventional companies. This has suggested that being shariah-compliant companies has brought unique and privilege features in its capital structure.